ANALYSIS THE IMPLEMENTATION OF HYGIENE AND SANITATION OF SNACK PRODUCTS IN THE UNIVERSITAS NEGERI PADANG CANTEEN - Wahyudi Putra, Rahmat (TEKNOLOGI MEDIS DAN JURNAL KESEHATAN UMUM, 2023)
Food is a basic need for human life. Various types of food are consumed with various ways of processing. There are so many things that can cause a food to be unsafe, one of which is due to contamination. Contamination that occurs in food and beverages can cause food to become a medium for disease. Thus, community efforts to be able to maintain food health and safety need to be increased through the application of hygiene and sanitation. Based on the Decree of the Minister of Health of the Republic of Indonesia Number 942/Menkes/SK/VII/2003 concerning Guidelines for Snack Food Sanitation Hygiene Requirements, several aspects are regulated in the handling of snack food, namely food handlers, equipment, water, food ingredients, food additives, serving and peddlers. The purpose of this study was to find out the description of the implementation of hygiene and sanitation of snack products in the Universitas Negeri Padang campus canteen. This research is a descriptive observational study with a quantitative approach using a questionnaire. The results of this study indicate that the level of implementation of hygiene and sanitation regarding the selection of materials and sanitation of equipment is in the excellent category, while the level of knowledge about food processing and food serving is in the range category good to excellent category.